WATER WELLS QUALITY ASSESSMENT USING WATER QUALITY INDEX FOR THE PURPOSES OF DRINKING OF M’ZAB WADI REGION - Benabderrahmane, H; Baba Amer, Z (university of el oued/جامعة الوادي, 2021)
The prese nt work aims to assess the groundwater quality using Water Quality Index (WQI which can be considered as major factor for cont rolling quality of water with regarded to drinking purposes . Water qualit y index is used to illustrate the general state of water quality in a single number . This study concerns specifically Daia area upstream region of M' z ab valley. Water samples have been collected at eighteen groundwater points in two year s 2016 and 2017. Then, different parameters a re analyzed and compared with Algerian standards for drinking water The hydrochemical study shows significant variations in physico c hemical measurement Also, t he obtained results of the water quality index in Daia region sh ow an excellent ranking with 94%, 88% in years respectively
Article
Keywords: Groundwater drinking water quality the hydrochemical WQI